2023
DOI: 10.1093/qjmed/hcad225
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting the risk of generalization for ocular-onset myasthenia gravis: a nationwide cohort study

Jingsi Wang,
Hongyu Zhou,
Hongxi Chen
et al.

Abstract: Summary Background The environmental effects on the prognosis of ocular myasthenia gravis (OMG) remain largely unexplored. Aim To investigate the association between specific environmental factors and the generalization of OMG. Design The cohort study was conducted in China based on a nationwide multicenter database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Higher rates of ocular myasthenia are appreciated in older American and Japanese populations ( 109 , 110 ), while a study in China found higher rates of ocular myasthenia in children ( 111 ), with differential susceptibility based on HLA-DQA1/DQB1 haplotypes ( 112 ). Environmental factors were suggested based on latitudinal variation in ocular myasthenia frequency ( 113 ). The miRNA 30-e-5P is a potential biomarker to predict generalization of ocular MG to widespread MG ( 114 ), but how it relates to disease pathology is not known.…”
Section: Cellular Pathogenesis Of Mgmentioning
confidence: 99%
“…Higher rates of ocular myasthenia are appreciated in older American and Japanese populations ( 109 , 110 ), while a study in China found higher rates of ocular myasthenia in children ( 111 ), with differential susceptibility based on HLA-DQA1/DQB1 haplotypes ( 112 ). Environmental factors were suggested based on latitudinal variation in ocular myasthenia frequency ( 113 ). The miRNA 30-e-5P is a potential biomarker to predict generalization of ocular MG to widespread MG ( 114 ), but how it relates to disease pathology is not known.…”
Section: Cellular Pathogenesis Of Mgmentioning
confidence: 99%